Resilient Nature Based Water Solutions (RNBWS) in the Middle East and North Africa (MENA region) - International Water Management Institute (International Water Management Institute, 2024)
The primary objective of Al Murunah (‘flexibility’ in Arabic) is to increase water security and support climate change adaptation in the MENA region by integrating nature-based solutions for water and agricultural water management. These integrated interventions, which Al Murunah calls resilient nature-based water solutions (RNBWS), are coupled with social and market mechanisms to support sustainability and transferability. The central premise of Al Murunah is that appropriately and collaboratively designed RNBWS can enhance water and food security in agricultural areas of MENA, thereby increasing the resilience of rural households and communities. Broadly speaking, RNBWS can enhance water availability (including via improvements in quality) and reduce agricultural water demand or otherwise increase its productivity. Simultaneously, they can support sustainable management of watersheds and agro-ecosystems to benefit human well-being and biodiversity.